Respuesta Serológica a la vacunación contra la Hepatitis B en personas viviendo con VIH en Cali, Colombia - Lina Marcela Muñoz-Solano (Infectio)
Introduction: Hepatitis B virus (HBV) and HIV coinfection is common, with reported prevalence of up to 20%. This coinfection is associated with an increased risk of chronicity and complications compared with the general population. HBV vaccination is the cornerstone of prevention; however, people living with HIV (PLWH) exhibit a reduce immune response to the vaccine. The objective of this study was to determine the incidence and factors associated with the lack of seroconversion after HBV vaccination in PLWH in Cali, Colombia.Materials and methods: This was a retrospective cohort study in two HIV outpatient clinics. We included HIV-confirmed adult patients admitted between 2017 and 2020, with no evidence of HBV infection and with under the protective levels of HBV surface antibodies (anti-HBs ≤10 IU/ml) on admission, who received at least one dose of HBV vaccine, and had reported anti-HBs post vaccination. The outcome was lack of seroconversion (anti-HBs ≤10 IU/ml post vaccination)Results: Of 512 patients screened, 73.8% (95% CI: 73.4–74.2) had anti-HBs ≤10 IU/ml on admission of whom 224 were included. The incidence of anti-HBs ≤10 IU/ml post vaccination was 39.7% (95% CI: 39.5–39.9). Age (aOR 1.03 95% CI: 1-1.05), CD4 count ≤ 200 cells (aOR 7.8 95% CI: 2–29.8), BMI >30 kg/m2(aOR 5.1 95% CI: 1.9–14.1), and smoking in females (aOR 6.8 95% CI: 1–81) were risk factors for lack of seroconversion. In contrast, two (aOR 0.2 95% CI: 0.06–0.9) or three (aOR 0.2 95% CI: 0.06–0.6) HBV vaccine doses instead of one were protective.Discussion: A significant proportion of PLWH are eligible for HBV vaccination in Cali. In those who received at least one HBV vaccine dose, the incidence of lack of seroconversion is comparable to reports in Latin America. The factors associated with lack of seroconversion could be considered to adjust the guidelines for HBV vaccination in PLWH in Colombia.